Direitos e libertação para o inexistente: as implicações da de-extinção. - Giles, Richard ((Des)troços: revista de pensamento radical, 2025)
De-extinction is an emerging biotechnological innovation that has seen a sudden uptick of media and investment attention, holding considerable implications for animal populations of all sorts. This paper, after providing an overview of de-extinction discourse, rhetoric, and ideas, contextualizes this innovation within the works of Catia Faria and Sue Donaldson & Will Kymlicka. Said contextualization provides impetus for animal theory to engage with de-extinction in more detail, and beyond an immediate rejection of the practice. De-extinction holds grave implications for animal populations that must be considered in theory, both to critique the practice, and to better understand the importance of theoretical framework in the context of the ongoing “animal turn” in political theory.